(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
This study investigated the seasonal variations in physicochemical parameters, plankton community structure, and fish species composition of Warwade Reservoir, Nigeria, from May to October. Monthly sampling was conducted to assess water quality variables including temperature, pH, dissolved oxygen (DO), electrical conductivity (EC), nitrate, and phosphate, and fish assemblages. Water samples for the determination of physicochemical parameters were collected at selected sampling points. Some parameters such as water temperature and dissolved oxygen were measured in situ (at the sampling site) using portable water quality meters. Other parameters were analyzed in the laboratory using standard methods, fish samples were collected from the catches of the fishermen and captured fish were identified to species level, counted and recorded, and data were subjected to analysis of variance (ANOVA) to determine monthly variations. Results showed significant monthly variation in temperature, pH, and phosphate concentration (P< 0.05), while DO, EC, and nitrate exhibited no significant differences (P>0.05). Water quality parameters largely remained within permissible limits, indicating generally good water quality, although dissolved oxygen levels were consistently below the recommended 5 mg/L threshold. A total of nine fish species were recorded, with Oreochromis niloticus, Coptodon zilli, and Sarotherodon galilaeus being the most dominant. Fish abundance varied significantly across months (P< 0.05), with peak abundance occurring during August and September, corresponding with increased plankton productivity and favorable hydrological conditions. The study demonstrates that seasonal hydrological dynamics and nutrient availability play critical roles in shaping the ecological structure and productivity of Warwade Reservoir. Continuous monitoring and sustainable fisheries management strategies are recommended to ensure long-term ecosystem health and resource sustainability.